Dinamika Pengembangan Wisata Halal Di Kota Pekanbaru - Lubis, Ema Fitri; Zubaidah, Evi; Ramailis, Neri Widya; Meldawati (Prodi Sosiologi Agama, 2022)
The development of halal-based tourism requires planning, Implementation, and control efforts, to create added value as desired. One is implementing the Indonesian halal tourism logo and the Halal Tourism Halal Logo. Halal Tourism is an additional service that is part of tourism. The research was conducted to analyze and explain the Implementation of Halal Tourism Development in Pekanbaru City. This research was conducted using indicators of Implementation according to Edward III, namely first Communication, second Resources, third Disposition and fourth bureaucratic structure. This type of research uses descriptive with qualitative methods. The study results are based on indicators of Communication, resources, disposition, and bureaucratic structure. Communication activities in the form of socialization by the implementor have been carried out through various media, namely social media, the web, and promotion through local television media. However, consistency still needs to be improved. Not a few of the community/business people themselves still need to understand the concept of halal tourism, steps in the Implementation of halal tourism development have been at the stage of making a decree (SK) Accelerating the Development of Halal Tourism. Halal certificates in several culinary businesses and restaurants must be implemented better. There are budget constraints owned by the Pekanbaru City Culture and Tourism Office, so the Implementation of halal tourism development activities has yet to be maximally achieved.